Letter - Birmingham Trades Council & Labour Party, 5 May 1926 (Birmingham)
1926-05-05 "Letter - Birmingham Trades Council & Labour Party, 5 May 1926" [g0372001.jpg], 5 May 1926, Birmingham Trades Council & Labour Party Local Organisation